220k views
1 vote
Which expression is equivalent to x^4 + 4x^2 - 45?

1 Answer

3 votes

Answer:


( {x}^(2) - 5)( {x}^(2) + 9) = 0

Explanation:

The given expresion is


{x}^(4) + 4 {x}^(2) - 45 = 0

We can rewrite this as:


({ {x}^(2)) }^(2) + 4 {x}^(2) - 45 = 0

We obtained a quadratic equation in x²

Let us split the middle term to get:


({ {x}^(2)) }^(2) + 9 {x}^(2) - 5{x}^(2) - 45 = 0

We factor by grouping to get:


{x}^(2) ( {x}^(2) + 9) - 5( {x}^(2) + 9) = 0

We factor further to get:


( {x}^(2) - 5)( {x}^(2) + 9) = 0

The correct answer is A.

Which expression is equivalent to x^4 + 4x^2 - 45?-example-1
User Chandra Eskay
by
5.0k points